Particles and Nuclei - Povh, Bogdan; Rith, Klaus; Scholz, Christoph; Zetsche, Frank; Rodejohann, Werner (Springer, 2015)
Since the first German edition of this textbook in 1993, many extensions and corrections of the text have been added in every further edition. For the present seventh English edition, the text of several chapters and also many figures have been thoroughly revised and updated, and plenty of additional information has been added. Werner Rodejohann joined the team of authors. He mainly cared about the chapters that deal with neutrinos and the Higgs particle. A new Chap. 11 has been added with the focus on neutrino properties, neutrino oscillations and Majorana neutrinos; additional aspects of the latter topic are summarised in Chap. 18. Chapter 12 has been extended by a discussion on spontaneous symmetry breaking, the Higgs potential and the experimental observation of the Higgs particle at the LHC. Updates on experimental results include new information about the elastic form factors of proton and neutron, in particular from JLab experiments (Chap. 6) and the final results for the proton structure function Fp 2 and charged-current cross-sections obtained by the experiments H1 and ZEUS at the HERA electron/positron-proton collider HERA (Chaps. 8, 10, 12). Chapter 15 has been substantially extended by a discussion of CP violation in the decay of neutral K- and B-mesons and its detailed investigation by fixed-target experiments with high-energy kaon beams at CERN and FNAL and the two B-factory experiments BaBar and BELLE. A section on the investigation of the nucleon’s spin structure in deep-inelastic lepton-nucleon scattering with polarised beams and targets has been added to Chap. 16.
An Introduction to the Physical Concepts